CCL2 promotes osteogenesis by facilitating macrophage migration during acute inflammation - Toya, Masakazu; Zhang, Ning; Tsubosaka, Masanori; Kushioka, Junichi; Gao, Qi; Li, Xueping; Chow, Simon Kwoon-Ho; Goodman, Stuart B. (Frontiers in Cell and Developmental Biology, 2023)
Novel minimally invasive strategies are needed to obtain robust bone healing in complex fractures and bone defects in the elderly population. Local cell therapy is one potential option for future treatment. Mesenchymal stromal cells (MSCs) are not only involved in osteogenesis but also help direct the recruitment of macrophages during bone regeneration via MSC-macrophage crosstalk. The C-C motif chemokine ligand 2 (CCL2) is an inflammatory chemokine that is associated with the migration of macrophages and MSCs during inflammation. This study investigated the use of CCL2 as a therapeutic target for local cell therapy. MSCs and macrophages were isolated from 10-12 weekold BALB/c male mice. Genetically modified CCL2 over-expressing MSCs were produced using murine CCL2-secreting pCDH-CMV-mCCL2-copGFP expressing lentivirus vector. Osteogenic differentiation assays were performed using MSCs with or without macrophages in co-culture. Cell migration assays were also performed. MSCs transfected with murine CCL2-secreting pCDH-CMV-mCCL2-copGFP expressing lentivirus vector showed higher levels of CCL2 secretion compared to unaltered MSCs (p < 0.05). Genetic manipulation did not affect cell proliferation. CCL2 did not affect the osteogenic ability of MSCs alone. However, acute (1 day) but not sustained (7 days) stimulation with CCL2 increased the alizarin red-positive area when MSCs were co-cultured with macrophages (p < 0.001). Both recombinant CCL2 (p < 0.05) and CCL2 released from MSCs (p < 0.05) facilitated macrophage migration. We demonstrated that acute CCL2 stimulation promoted subsequent osteogenesis in co-culture of MSCs and macrophages. Acute CCL2 stimulation potentially facilitates osteogenesis during the acute inflammatory phase of bone healing by directing local macrophage migration, fostering macrophage-MSC crosstalk, and subsequently, by activating or licensing of MSCs by macrophage pro-inflammatory cytokines. The combination of CCL2, MSCs, and macrophages could be a potential strategy for local cell therapy in compromised bone healing.